Exploring the Dynamics of Agripreneurship Perception and Intention among the Nigerian Youth - Kenechukwu Ikebuaku; Mulugeta Dinbabo (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2023)
With more than half of young Nigerians either unemployed or underemployed, the problem of youth unemployment poses a serious threat to the social, political, and economic development of the country. Thus, there has been a concerted effort by the government and other stakeholders to address this perennial challenge. Owing to its enormous growth opportunities, agriculture is considered a strategic sector for addressing Nigeria's problem of youth unemployment. However, the lack of youth participation has hampered the growth of the sector. This study investigated the dynamics of agripreneurship perception and intention in order to provide insight to policymakers on how best to develop the agricultural sector and tackle youth unemployment through the engagement of young people in the sector. It also explored agricultural entrepreneurship as a valuable function for young people in Nigeria. A sample of 1,013 recent young graduates took part in this study, which engaged both quantitative and qualitative methodologies. The quantitative analysis was conducted using linear regression and multinomial response models. Additionally, Sen’s capability approach was used as the work’s theoretical framework. The results established that Nigerian youths display a positive perception and intention towards agripreneurship engagement. It also found that participation in entrepreneurship programs, course of study, family income, perceived availability of markets, and infrastructural facilities are determinants of youth’s agripreneurship perception and intention. On the other hand, the study found that the freedom to control one’s time, the expression of one’s passion, and the need to eradicate poverty are reasons young Nigerians value agripreneurship. This study serves as the debut of research endeavours that theoretically evaluate agripreneurship undertakings as valuable functionings using the capability approach. Furthermore, by examining factors that affect agripreneurship perception and intention, the study offers fresh policy insights for youth entrepreneurship and employment creation in the agricultural sector.